Family Financial Management with Religiosity Perspective - Agustin Kustiwi, Irda (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research aims to explore the concept of family financial management which is closely related to the divine perspective. The research method chosen by the author is divine phenomenology. The results of the informants produced one finding, that the higher the religious understanding obtained from religious studies does not necessarily make a family smart in planning and managing their household finances. Although there are some exceptions, there are informants in the lower class who are able to manage their household finances well so that they can prepare for future needs wisely.